2005
DOI: 10.1021/jm049276y
|View full text |Cite
|
Sign up to set email alerts
|

Structure-Based Characterization and Optimization of Novel Hydrophobic Binding Interactions in a Series of Pyrrolidine Influenza Neuraminidase Inhibitors

Abstract: The structure-activity relationship (SAR) of a novel hydrophobic binding interaction within a subsite of the influenza neuraminidase (NA) active site was characterized and optimized for a series of trisubstituted pyrrolidine inhibitors modified at the 4-position. Previously, potent inhibitors have targeted this subsite with hydrophilic substituents such as amines and guanidines. Inhibitor-bound crystal structures revealed that hydrophobic substituents with sp(2) hybridization could achieve optimal interactions… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
38
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 58 publications
(40 citation statements)
references
References 33 publications
2
38
0
Order By: Relevance
“…Total 32 molecule samples are used in the training set. The molecular structures and bioactivities pIC 50 of the 32 molecules 24 are listed in Table1. According to the standard 3D-QSAR methods, such as CoMFA and CoMSIA, a cubic grid is set up surrounding the aligned ligand molecules and thousands upon thousands potential values at these grid points are calculated.…”
Section: Calculations and Resultsmentioning
confidence: 99%
“…Total 32 molecule samples are used in the training set. The molecular structures and bioactivities pIC 50 of the 32 molecules 24 are listed in Table1. According to the standard 3D-QSAR methods, such as CoMFA and CoMSIA, a cubic grid is set up surrounding the aligned ligand molecules and thousands upon thousands potential values at these grid points are calculated.…”
Section: Calculations and Resultsmentioning
confidence: 99%
“…In total, 126 known NIs were prepared in this study, and their bioactivities against influenza A virus were mainly taken from the literature [12,16,[22][23][24][25][26] ( Table 1). IC 50 values are available for most inhibitors except for a series of pyrrolidine NIs [12], for which IC 50 values were calculated from K i values using the Cheng-Prusoff equation [27].…”
Section: Methodsmentioning
confidence: 99%
“…Rational drug design utilizing available X-ray crystal structures of NA-inhibitor complexes has led to the discovery of some six-membered ring NIs including those two marketed drugs mentioned above [9,10]. Recently, a series of pyrrolidine and cyclopentane-based NIs were also developed by employing an iterative structurebased methods [12,13], some of which have shown equal or better efficacies on comparison with oseltamivir carboxylate and zanamivir [14]. Correlating the physicochemical properties of compounds or the computed binding energies with inhibitory activities is believed to gain an insight into the interaction mechanism of NA to inhibitors, and recently Verma et al reported 17 quantitative structure-activity relationships (QSAR) for different sets of NIs [15].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Whereas oseltamivir can be described as a cyclohexenyl derivative, there are a number of cyclopentane and pyrrolidine derivatives that have been described as neuraminidase inhibitors: peramivir (RWJ -270201, BCX -1182) 67 -69 and other cyclopentane 69,70 and cyclopentane amide 71 derivatives as well as a variety of pyrrolidine derivatives, including A -192558, 72 A -315675, 73 -75 and other pyrrolidines 76 (Fig. 1.8 ).…”
Section: Neuraminidase Inhibitors: Peramivir and Other Cyclopentane Omentioning
confidence: 99%